2016
DOI: 10.1159/000445433
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Regulatory T Cells as a Novel Mechanism Underlying the Therapeutic Action of Kakkonto, a Traditional Japanese Herbal Medicine, in a Murine Food Allergy Model

Abstract: Background: The number of patients with food allergy (FA) has dramatically increased. Although satisfactory drug therapies for FA are not available, we have found that kakkonto, a traditional Japanese herbal medicine, suppressed the occurrence of allergic symptoms in an FA mouse model. Thus, we investigated whether kakkonto could regulate the activation and differentiation of T cells in the colon. Methods: BALB/c mice were systemically sensitized and then orally challenged with ovalbumin. FA mice were orally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The induction of Treg cells and IL-10 has been shown to play an important role in maintaining peripheral T-cell tolerance, which is essential for normal immune responses and successful immunotherapy of allergic disorders [32,34,35]. We found that there were increased relative numbers of CD4+CD25+FOXP3+ cells in both the dLNs and the spleen in PLL-pAra h 2-treated mice, which were much higher than those of pAra h 2-treated mice.…”
Section: Discussionmentioning
confidence: 72%
“…The induction of Treg cells and IL-10 has been shown to play an important role in maintaining peripheral T-cell tolerance, which is essential for normal immune responses and successful immunotherapy of allergic disorders [32,34,35]. We found that there were increased relative numbers of CD4+CD25+FOXP3+ cells in both the dLNs and the spleen in PLL-pAra h 2-treated mice, which were much higher than those of pAra h 2-treated mice.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, egg food allergy is a relevant area of allergy research and egg food allergy experimental models often serve as tools in the field. Maeta et al [54] published a study that aimed to determine the dosing of dietary egg white supplementation required for an oral immunotherapy regimen in an egg white allergic mouse model. The findings showed that 1% egg white resulted in desensitization and immune tolerance with lower incidences of diarrhea, lower ovomucoid-specific IgE, IgA, and IgG2a, lower percentages of CD4 + Foxp3 + cells, and higher IFN-γ and IL-10 spleen lymphocyte secretions.…”
Section: Food Allergymentioning
confidence: 99%
“…Induction of FA was performed as previously described [21,22]. Briefly, mice were sensitized twice at a 2-week interval with 100 μg ovalbumin (OVA, albumin from chicken egg white grade V, Sigma-Aldrich, St. Louis, MO, USA) in the presence of 2 mg aluminum hydroxide (Thermo Scientific, Rockford, IL, USA) as an adjuvant by intraperitoneal injection.…”
Section: Experimental Protocol Of the Murine Food Allergy Modelmentioning
confidence: 99%
“…The most important aspect contributing to the frequent use of kakkonto is that kakkonto is a highly effective and safe medicine for the treatment of the common cold [17,18], influenza [19], allergic rhinitis [20] and diarrhea either as the sole source of therapy or in combination with modern Western medicines. We have previously demonstrated that kakkonto suppresses the occurrence of allergic symptoms in a murine FA model [21] and kakkonto induces Foxp3 + CD4 + regulatory T cells (Tregs) in the colon as a novel mechanism underlying the therapeutic action [22]. It is reported that allergen-specific immunotherapy increases the production of local and systemic Foxp3 + CD4 + Tregs as an essential step in patients [23,24] and experimental models [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%